Hubungan Antara Pengetahuan, Sikap Pasien, Dan Dukungan Keluarga Dengan Keteraturan Pengobatan Pasien Tuberkulosis Paru Di Kabupaten Klaten - Erawati, Lely; Suryani, Nunuk; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background : Regularity of pulmonary tuberculosis treatment are affected by many factors such as knowledge, attitudes of patients, and family support.This study aimed to analyze the relationship between knowledge, attitudes of patient, andfamily support, and regularity of tuberculosis treatment. Methods : This was an analytic observational study using a cross sectionaldesign.A sample of 57 pulmonary tuberculosis patients who had been undertaking anti-tuberculosis direct observed treatment short course in Klatendistrict, Central Java, for the past two years were studied. The data on the independent variables including knowledge, patient attitude, and family support, were collected using questionnaire. The secondary data on regularity of tuberculosis treatment were taken from the reporting and recording system at health center and district health office. The relationshipbetween knowledge, patient attitude,and family support and regularity of treatment were analyzed using multiple logistic regression model. Odds Ratio and its 95CI% were estimated. Results : Tuberculosis patientswho had high tuberculosis knowledge had four timeshigher probability to undertake regular treatment than those with low knowledge(OR =4.40 ; CI 95 % = 1.08 to 17.89 ; p = 0.030). Patients with good attitude had three timeshigherprobability to undertake regular treatment than those with poor attitude (OR = 3.67 ; CI95 % = 1.02 to 13.42 ; p = 0.043). Patients with strong family support were twice more likely to undertake regular treatment than those with weak family support (OR = 2.22; CI 95 % = 0.54 to 9.14; p = 0.261). Conclusion: There is a positive relationship between knowledge, patient attitude, and Â family support, and regularity of pulmonary tuberculosis treatment. Keywords: Pulmonary tuberculosis, knowledge, patient attitude, family support, regular treatment